Efficacy and safety of short vs. Standard long regimens for multidrug- resistant tuberculosis: a network meta-analysis - G R Simanjuntak, Josephine; A K Gandhy, Made; Sadha, Kynthia (ACTA Medical Health Sciences, 2025)
Drug-resistant tuberculosis (DR-TB) remains a critical health concern, particularly in high- burden regions like Indonesia. Shorter treatment regimens have been proposed to improve outcomes for multidrug- and rifampicin-resistant tuberculosis (MDR/RR-TB). This systematic review and Bayesian network meta-analysis aimed to evaluate the efficacy and safety of these shorter regimens. Using PRISMA-NMA guidelines, we systematically searched multiple databases, including PubMed, Cochrane, Scopus, WOAJ, and WOS, for studies published between 2014 to 2024. We included 23 eligible studies comprising a total of 6,343 MDR/RR- TB patients. Results showed that treatment with a 9-12 month regimen, specifically Kanamycin (Km)/Capreomycin (Cm), Moxifloxacin (Mfx)/Levofloxacin (Lfx), Prothionamide (Pto), Clofazimine (Cfz), Pyrazinamide (Z), Ethambutol (E), High-dose Isoniazid (Hh) demonstrated almost twice the probability of favorable outcomes defined as cure or treatment completion, compared to the standard regimens [RR 1.66 (95%CrI 1.34;2.04), P=0.0094]. Additionally, the 6-month regimen Bedaquiline (Bdq), Pretomanid (Pa), Linezolid (Lzd), Moxifloxacin (Mfx) also showed significantly higher favorable outcomes [RR 1.59 (95%CrI 1.29;2.03), P<0.001]. For safety outcomes, regimens containing bedaquiline, such as the 6-month Bdq, Pa, Lzd, Mfx regimen, had a 38% reduction in the risk of adverse events compared to the standard [RR 0.623 (95%CrI 0.280;1.29), P < 0.0001]. This was followed by the 6-month Bdq, Pa, Lzd and the Bdq, Pa, Lzd, Cfz regimen, which also showed lower risks of adverse events. In conclusion, shorter MDR/RR-TB regimens, especially those containing bedaquiline, appear to enhance cure rates while reducing adverse effects, supporting current WHO guidelines for 6-month treatment options DOI : 10.35990/amhs.v3n3.p151-162 REFERENCES World Health Organization. Tuberculosis. 2024. Available from: https://www.who.int/news-room/fact-sheets/detail/tuberculosis (accessed 10 October 2024). Perhimpunan Dokter Paru Indonesia (PDPI). Buku Pedoman TBC 2021. 2021. Available from: https://bukupdpi.klikpdpi.com/wp-content/uploads/2022/08/BUKU-GUIDELINE-TB-2021.pdf (accessed 10 October 2024). World Health Organization. Tuberculosis: Multidrug-resistant Tuberculosis (MDR-TB). 2018. Available from: https://www.who.int/news-room/questions-and-answers/item/tuberculosis-multidrug-resistant-tuberculosis-(mdr-tb) (accessed 10 October 2024). Kementerian Kesehatan Republik Indonesia. Laporan Program Penanggulangan Tuberkulosis Tahun 2022. 2023. Available from: https://www.tbindonesia.or.id/wp-content/uploads/2023/09/Laporan-Tahunan-Program-TBC-2022.pdf (accessed 10 October 2024). Jang JG, Chung JH. Diagnosis and treatment of multidrug-resistant tuberculosis. Yeungnam Univ J Med. 2020;37(4):277–85. Soedarsono S, Mertaniasih NM, Kusmiati T, Permatasari A, Ilahi WK, Anggraeni AT. Characteristics of previous tuberculosis treatment history in patients with treatment failure and the impact on acquired drug-resistant tuberculosis. Antibiotics. 2023;12(3):598. Yew WW, Koh WJ. Emerging strategies for the treatment of pulmonary tuberculosis: promise and limitations? Korean J Intern Med. 2015;31(1):15–29. Trevisi L, Hernán MA, Mitnick CD, Khan U, Seung KJ, Rich ML, et al. Effectiveness of bedaquiline use beyond six months in patients with multidrug-resistant tuberculosis. Am J Respir Crit Care Med. 2023;207(11):1525–32. Putra ON, Yulistiani Y, Soedarsono S, Subay S. Early efficacy of individual regimens containing bedaquiline in patients with drug resistant tuberculosis. Asian Pac J Trop Med. 2023;16(4):169–75. Gill CM, Dolan L, Piggott LM, McLaughlin AM. New developments in tuberculosis diagnosis and treatment. Breathe. 2022;18(1):210149. Padmapriyadarsini C, Vohra V, Bhatnagar A, Solanki R, Sridhar R, Anande L, et al. Bedaquiline, delamanid, linezolid, and clofazimine for treatment of pre-extensively drug-resistant tuberculosis. Clin Infect Dis. 2022;76(3):e938–46. Mok J, Lee M, Kim DK, Kim JS, Jhun BW, Jo KW, et al. 9 months of delamanid, linezolid, levofloxacin, and pyrazinamide versus conventional therapy for fluoroquinolone-sensitive multidrug-resistant tuberculosis (MDR-END): a multicentre, randomised, open-label phase 2/3 non-inferiority trial in South Korea. Lancet. 2022;400(10362):1522–30. Nyang’wa BT, Berry C, Kazounis E, Motta I, Parpieva N, Tigay Z, et al. A 24-week, all-oral regimen for rifampin-resistant tuberculosis. N Engl J Med. 2022;387(25):2331–43. Esmail A, Oelofse S, Lombard C, Perumal R, Mbuthini L, Goolam Mahomed A, et al. An all-oral 6-month regimen for multidrug-resistant tuberculosis: a multicenter, randomized controlled clinical trial (the NExT Study). Am J Respir Crit Care Med. 2022;205(10):1214–27. Nunn AJ, Phillips PPJ, Meredith SK, Chiang CY, Conradie F, Dalai D, et al. A trial of a shorter regimen for rifampin-resistant tuberculosis. N Engl J Med. 2019;380(13):1201–13. Tang S, Yao L, Hao X, Liu Y, Zeng L, Liu G, et al. Clofazimine for the treatment of multidrug-resistant tuberculosis: prospective, multicenter, randomized controlled study in China. Clin Infect Dis. 2015;60(9):1361–7. Duan H, Chen X, Li Z, Pang Y, Jing W, Liu P, et al. Clofazimine improves clinical outcomes in multidrug-resistant tuberculosis: a randomized controlled trial. Clin Microbiol Infect. 2019;25(2):190–5. Garcia-Prats AJ, Frias M, van der Laan L, De Leon A, Gler MT, Schaaf HS, et al. Delamanid added to an optimized background regimen in children with multidrug-resistant tuberculosis: results of a Phase I/II clinical trial. Antimicrob Agents Chemother. 2022;66(5):e0214421. von Groote-Bidlingmaier F, Patientia R, Sanchez E, Balanag V, Ticona E, Segura P, et al. Efficacy and safety of delamanid in combination with an optimised background regimen for treatment of multidrug-resistant tuberculosis: a multicentre, randomised, double-blind, placebo-controlled, parallel group phase 3 trial. Lancet Respir Med. 2019;7(3):249–59. Yao G, Zhu M, Nie Q, Chen N, Tu S, Zhou Y, et al. Improved outcomes following addition of bedaquiline and clofazimine to a treatment regimen for multidrug-resistant tuberculosis. J Int Med Res. 2023;51(1):3000605221148416. Diacon AH, Pym A, Grobusch MP, de los Rios JM, Gotuzzo E, Vasilyeva I, et al. Multidrug-resistant tuberculosis and culture conversion with bedaquiline. N Engl J Med. 2014;371(8):723–32. Song Y, Shu W, Pei Y, Du J, Wu G, Wang H, et al. Nine months of bedaquiline, linezolid, levofloxacin, clofazimine, and cycloserine chemotherapy for rifampicin/multidrug-resistant tuberculosis: a multicenter, randomized, open-label non-inferiority trial in China. BMC Med. 2024;22(1):465. Dooley KE, Rosenkranz SL, Conradie F, Moran L, Hafner R, von Groote-Bidlingmaier F, et al. QT effects of bedaquiline, delamanid, or both in patients with rifampicin-resistant tuberculosis: a phase 2, open-label, randomised, controlled trial. Lancet Infect Dis. 2021;21(7):975–83. Nyang’wa BT, Berry C, Kazounis E, Motta I, Parpieva N, Tigay Z, et al. Short oral regimens for pulmonary rifampicin-resistant tuberculosis (TB-PRACTECAL): an open-label, randomised, controlled, phase 2B-3, multi-arm, multicentre, non-inferiority trial. Lancet Respir Med. 2024;12(2):117–28. Du Y, Qiu C, Chen X, Wang J, Jing W, Pan H, et al. Treatment outcome of a shorter regimen containing clofazimine for multidrug-resistant tuberculosis: a randomized control trial in China. Clin Infect Dis. 2020;71(4):1047–54. Hassane-Harouna S, Cherif GF, Ortuno-Gutierrez N, Cisse D, Camara LM, Diallo BD, et al. Better programmatic outcome with the shorter regimen for the treatment of multidrug-resistant tuberculosis (MDR-TB) in Guinea: a retrospective cohort study. PLoS ONE. 2020;15(8):e0237355. Mleoh L, Mziray SR, Tsere D, Koppelaar I, Mulder C, Lyakurwa D. Shorter regimens improved treatment outcomes of multidrug-resistant tuberculosis patients in Tanzania in 2018 cohort. Trop Med Int Health. 2023;28(5):357–66. Mok J, Lee M, Kim DK, Kim JS, Jhun BW, Jo KW, et al. 9 months of delamanid, linezolid, levofloxacin, and pyrazinamide versus conventional therapy for fluoroquinolone-sensitive multidrug-resistant tuberculosis (MDR-END): a multicentre, randomised, open-label phase 2/3 non-inferiority trial in South Korea. Lancet. 2018;400(10362):1522–30. Ronnachit D, Cros DP, Khamraev A, Lister D, Ronnachit A, Berry C, et al. Comparing shorter with conventional MDR-TB treatment in Uzbekistan: 2-month culture-conversion rates and treatment outcomes. F1000Research. 2017;6:913. Myemba DT, Bwire GM, Sambayi G, Maganda BA, Njiro BJ, Ndumwa HP, et al. Clinical characteristics and treatment outcomes of patients with MDR tuberculosis in Dar Es Salaam region, Tanzania. JAC Antimicrob Resist. 2020;2(4):dlaa108. Wahid A, Ghafoor A, Khan AW, Al-Worafi YM, Latif A, Shahwani NA, et al. Comparative effectiveness of individualized longer and standardized shorter regimens in the treatment of multidrug resistant tuberculosis in a high burden country. Front Pharmacol. 2022;13:973713. Zhdanova E, Goncharova O, Davtyan H, Alaverdyan S, Sargsyan A, Harries AD, et al. 9-12 months short treatment for patients with MDR-TB increases treatment success in Kyrgyzstan. J Infect Dev Ctries. 2021;15(9.1):66S–74S.